Western Modern Ideas in the Writings of Some Algerian Elites (Inheritance Issues in "The Right Approach in French Jurisprudence" Book as a model) - Bendris, zakaria; TOUNSI, Abdul Rahman (The Algerian Historical Journal, 2026)
The Western modern intellectual baggage brought by the French occupation to Algeria, colonial modernity, was able to create several contradictory binaries that carried means of attraction and polarization on the one hand, and means of physical and symbolic violence on the other, It sought to destroy traditional institutions and cancel all the values on which Algerian society was founded, and this was met with rejection and resistance. At the same time, it sought to spread secularism and the values of progress, equality, freedom, citizenship, democracy, and liberalism. This work sheds light on the issue of inheritance in Algerian writings influenced by Western thought, by taking book entitled "The Right Approach" omar ben brihmat as a focus of study, by including a set of elements, the most important of which are the entry of liberal modern ideas into Algeria, and his perceptions towards the issue of inheritance through his book The Right Approach.